Is intravenous recombinant plasminogen activator effective up to 4.5 h after onset of ischemic stroke? - Rothwell, P (2009)
Randomized, controlled trials and subsequent observational studies in routine clinical practice have shown that intravenous recombinant tissue plasminogen activator is safe and effective when used in selected patients within 3h of the onset of acute ischemic stroke. Results of the ECASS III (European Cooperative Acute Stroke Study III) trial have now confirmed the finding of a previous meta-analysis of data from individual patients from smaller trials, which showed that the time-window for benefit actually extends to 4.5h. However, the absolute benefit of treatment falls substantially with time after the onset of ischemic stroke and clinicians should, therefore, still aim to treat patients with intravenous recombinant tissue plasminogen activator within 90 min of stroke onset, if at all possible. Ongoing trials aim to determine whether eligibility for thrombolysis can be extended in other ways, such as to patients aged over 80 years, patients with severe stroke, or patients with lacunar stroke.